KARAKTERISTIK KANDUNGAN KIMIAWI DAN SIFAT SENSORI TEH IPOMOEA PESCAPRAE BERDASARKAN VARIASI PROSES PENGERINGAN - Pratama, Ginajar; Hasanah, Afifah Nurazizatul; Aditia, Rifki Prayoga; Muttaqin, Muhammad Iqbal; Rosita, Wiwit; Arisanti, Nabila; Yovanni, Ulfi Rahma; Yasmin, Ismi Illiyya; Ramadhan, Muhammad Azky Mamun; Khodijah, Khodijah (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2024)
Ipomoea pescaprae is a wild plant that grows in coastal areas and can beused as raw material for making tea with its advantages as a traditionalmedicine such as making herbal medicine to treat diuretic disorders,gonorrhea and pain. Tea is one of the healthiest drinks that is consumedand processed directly into powder using the drying method. The dryingmethod used is using an oven, roasting and sunlight. The practicum willbe held on May 3 2024 at 07.30 WIB until completion. Located at theAquatic Products Technology Laboratory Fisheries Department, Facultyof Agriculture, Sultan Ageng Tirtayasa University. The aim of thisresearch is to determine the effect of the drying process on theorganoleptic quality of Ipomoea pescaprae tea and to find out the besttreatment in the drying process. The highest pH is 7.44 in sun drying.RGB oven drying produces acid green color, roasting produces olivecolor, sun produces pastel green color. Based on the organoleptic testresults, it can be concluded that the dominant panelists liked oven-dryingtea because it has more attractive appearance and color values.